Estudo de melhorias na linha de produção de uma indústria automobilística multinacional - Felix, Marcus Vinicius Candido (2018)
Given the current economic scenario in Brazil, the automobile industry sector of the country is still recovering its economic stability. The application of lean manufacturing concepts generates a competitive advantage by eliminating the inherent inefficiencies of the system. The focus of this project was to propose improvements to cellular manufacturing in a multinational automobile company in order to meet the new customer’s demand. Therefore, the wastes of the production system were identified and reduced. The literature review informed the choice of methods that would best meet the goal of this study. These methods included the study of production times, the application of lean manufacturing tools, proposals for the layout changes and economic feasibility. In order to reach the goal of this project, techniques such as value flow mapping, methods-time measurement, spaghetti diagram, systematic layout planning and payback were used. As a result, layout changes and improvements were proposed and their benefits were described.